Students’ Perception Towards Integrating Quizizz Application in Basic English Grammar Lesson - Anggraini Katili, Yayu (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to describe the students’ perceptions on using Quizizz, a tool for online gamified quiz, in Basic English Grammar lesson for the first-semester students of English Education Department, State University of Manado. This research uses a qualitative descriptive method by collecting data using observation and closed ended questionnaires with 30 students. It explores students' views on the effectiveness, ease of use, and motivational impact of Quizizz. The findings show that most students have positive opinions about the application, with many agreeing that Quizizz enhances their grammar learning, makes lessons more enjoyable, and is user-friendly. Quizizz was also found to encourage independent learning and facilitate engagement with the material. Despite the overall positive feedback, some students expressed concerns about the tool’s applicability to subjects beyond grammar. These results suggest that while Quizizz is effective for teaching Basic English Grammar, further adaptation may be needed to expand its use in other areas of study. Overall, Quizizz proves to be a valuable educational tool.